1. Tìm giới hạn : [TEX]I=\lim_{x\rightarrow 1}(\frac{m}{1-x^m}-\frac{n}{1-x^n}) m,n\epsilon Z^+[/TEX]
2.chứng minh rằng nếu n là số nguyên ,[TEX]n \geq 1[/TEX] thì :[TEX](1+\frac{1}{n+1})^{n+1}>(1+\frac{1}{n})^n[/TEX]
[TEX]I=\lim_{x\rightarrow 1}(\frac{m}{1-x^m}-\frac{1}{x-1})-(\frac{n}{1-x^n}-\frac{1}{x+1})][/TEX]
[TEX]I=\lim_{x\rightarrow 1}(\frac{m-(1+x+x^2+...+x^{m-1})}{1-x^m}-\frac{n-(1+x+x^2+...+x^{n-1})}{1-x^n}) [/TEX]
[TEX]I=\lim_{x\rightarrow 1}(\frac{(1-x)+(1-x^2)+....+(1-x^{m-1})}{(1-x)(1+x+x^2+...+x^{m-1})}-\frac{(1-x)+(1-x^2)+...+(1-x^{n-1})}{(1-x)(1+x+x^2+..+x^{n-1})}) [/TEX]
[TEX]I=\lim_{x\rightarrow 1}(\frac{1+(1+x)+..+(1+x+...+x^{m-2})}{1+x+x^2+....+x^{m-2}}-\frac{1+(1+x)+....+(1+x+...+x^{n-2}}{1+x+x^2+....+x^{n-1}})[/TEX]
[TEX]I=\frac{1+2+...+(m-1)}{m}-\frac{1+2+...+(n-1)}{n}[/TEX]
[TEX]I=\frac{m(m-1)/2}{m}-\frac{n(n-1)/2}{n}=\frac{m-1}{2}-\frac{n-1}{2}=\frac{m-n}{2}[/TEX]
2.chứng minh rằng nếu n là số nguyên ,[TEX]n \geq 1[/TEX] thì :[TEX](1+\frac{1}{n+1})^{n+1}>(1+\frac{1}{n})^n[/TEX]
[TEX]BDT \Leftrightarrow 1+\frac{1}{n+1}> \sqrt[n+1]{(1+\frac{1}{n})^n}[/TEX]
[TEX]1+\frac{1}{n+1}=\frac{n+2}{n+1}=\frac{1+n(1+\frac{1}{n}}{n+1}[/TEX]
[TEX]\frac{1+(1+\frac{1}{n})+....+(1+\frac{1}{n})}{n+1}\geq \sqrt[n+1]{(1+\frac{1}{n})^n}[/TEX]
[TEX]DONE[/TEX]